1984
DOI: 10.1093/jac/14.suppl_c.83
|View full text |Cite
|
Sign up to set email alerts
|

Serum and sputum concentrations of enoxacin after single oral dosing in a clinical and bacteriological study

Abstract: Fifteen patients admitted to hospital with acute purulent exacerbations of chronic bronchitis were treated with enoxacin by mouth (three 200 mg capsules twice daily) for ten days. Sputum was cultured before, during and after the treatment course. Serum and sputum concentrations were measured microbiologically at intervals on the first treatment day. Blood was assayed before, and 1, 1 1/2, 2, 2 1/2, 3, 5 and 7 h after the first dose and purulent unhomogenized sputum was tested in samples collected 0-2, 2-4, 4-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…In some of these patients, this interaction gave rise to signs and symptoms of theophylline toxicity (Davies et al, 1984;Wijnands et al, 1985a). The present study confirms this interaction in subjects with stable pulmonary disease, whose only simultaneous treat-…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In some of these patients, this interaction gave rise to signs and symptoms of theophylline toxicity (Davies et al, 1984;Wijnands et al, 1985a). The present study confirms this interaction in subjects with stable pulmonary disease, whose only simultaneous treat-…”
Section: Resultssupporting
confidence: 82%
“…These high theophylline concentrations resulted in severe complaints of nausea, vomiting, tachycardia or agitation for some of the patients (Wijnands et al, 1984;Davies et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in plasma theophylline concentration appeared to be independent of enoxacin dose (800-1200 mg day-'). Davies et al (1984) Time after last theophylline dose (h) Figure 2 Elimination of theophylline in a single patient during enoxacin treatment (0) and 1 week after enoxacin had been stopped (-).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous treatment with drugs such as allopurinol (Manfredi & Vesell, 1981), cimetidine (Jackson et al, 1981;Reitberg et al, 1981), erythromycin (Prince et al, 1981), troleandomycin (Weinberger et al, 1977), can cause decreased theophylline clearance, whereas coadministration of phenobarbitone (Landay et al, 1978), phenytoin (Marquis et al, 1982) and isoprenaline (Hemstreet et al, 1982) In a previous study with enoxacin in respiratory tract infections by Davies et al (1984), the drug had to be discontinued in 9 of 15 patients because of side effects mainly related to the digestive system; seven of these patients used concomitant theophylline medication. In a clinical study with oral enoxacin in patients with a respiratory tract infection we observed unexpectedly high plasma theophylline concentrations causing complaints and symptoms of theophylline toxicity such as nausea and vomiting (Wijnands et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The MICs of enoxacin and norfloxacin for new colonizing microorganisms were determined by an agar dilution method. Breakpoints of 2.0 mg/liter for enoxacin and of 0.5 mg/liter for norfloxacin were chosen on the basis of previous pharmacokinetic studies (1,8,16).No enoxacin or norfloxacin activity was found in any fecal specimen obtained pretreatment or on day 21. The mean concentration of enoxacin on day 7 was 350 mg/kg of feces (range, 100 to 500 mg/kg), and the mean concentration of norfloxacin on day 7 was 950 mg/kg of feces (range, 440 to …”
mentioning
confidence: 99%